Assessment of the Budesonid Protective Effects in Patients with Cardio-Respiratory Comorbidity During Coronary Bypassing with Artificial Circulation - E. A. Sergeev; B. I. Geltser; V. N. Kotelnikov; A. E. Tarasov; V. Yu. Velichkin; A. A. Silaev (Вестник анестезиологии и реаниматологии)
The objective: evaluation of the effect of budesonide and low-volume mechanical ventilation (LVMV) on pulmonary volemia, oxygen transport and respiratory biomechanics in patients with concurrent ischemic heart disease (IHD) and chronic obstructive pulmonary disease (COPD) during coronary artery bypass grafting (CABG) with artificial circulation (AC).Subjects and Methods. 50 patients with concurrent IHD and COPD were enrolled in the study. During AC, patients of Group I (20 people) received mechanical ventilation with the peak inspiratory pressure of 15 mbar, tidal volume of 3‒4 ml/kg, positive end-expiratory pressure of 5 mbar in combination with inhalation of nebulized budesonide. In Group II (30 people), the similar isolated respiratory support was provided. Pulmonary blood volume, indices of extravascular lung water (EVLW), pulmonary vascular permeability (PVPI), oxygen delivery (DO2I) and consumption (VO2I), oxygen extraction ratio (O2ER), pulmonary shunt fraction (Qs/Qt), oxygenation index were determined. The study consisted of 3 stages: before AC, after its completion and one day after CABG.Results. Before CABG, the EVLW index in all patients exceeded the standard level by 67‒72%. After weaning from AC, it decreased by 23% in Group I and by 8% in Group II. In patients receiving budesonide, PVPI significantly decreased after artificial circulation, while in patients from Group II, it remained unchanged. DO2I and O2ER in all patients were within the reference range, and VO2I was below it with a minimum value in Group II after weaning from AC. In this cohort, the Qs/Qt level was significantly higher, while OI was lower versus patients from Group I. Among patients who received budesonide immediately after AC and 2 hours after it, pulmonary resistance decreased while lung compliance increased. In Group II, those parameters changed oppositely. In Group I, one case of hydrothorax was recorded, and in Group II, 2 patients were diagnosed with polysegmental pneumonia and 2 patients – with pneumothorax. The median duration of mechanical ventilation in the postoperative period made 220 minutes in Group I, and 290 minutes in Group II (p = 0.018).Conclusion. In patients with concurrent IHD and COPD, use of the combination of low-volume mechanical ventilation and inhalation of nebulized budesonide during AC stabilizes the volemic status of the lungs, improves the oxygenating function and respiratory biomechanics in the postperfusion and early postoperative periods of CABG.